(untitled) (Physical Education, Health and Social Sciences, 2026)
In this study, a comprehensive first-principles investigation of the structural, elastic, electronic, optical, and thermoelectric properties of the ternary intermetallic compounds HfBeIr2 and TiBeIr2 is presented. The calculations were performed within the framework of density functional theory using the full-potential linearized augmented plane wave method. Structural optimization confirms that both compounds crystallize in a stable cubic Fm-3m phase, with TiBeIr2 exhibiting a reduced lattice parameter and enhanced mechanical rigidity compared to HfBeIr2. The calculated elastic constants satisfy the mechanical stability criteria, indicating that both materials are mechanically stable, stiff, and exhibit slight elastic anisotropy. Electronic band structure and density of states analyses reveal the metallic nature of both compounds, with dominant contributions from transition metal d-orbitals near the Fermi level. Optical properties demonstrate characteristic metallic behavior, including high reflectivity in the infrared and visible regions and strong absorption in the ultraviolet range, suggesting potential applications in optoelectronic and coating technologies. Thermoelectric properties were evaluated using Boltzmann transport theory, revealing a clear contrast between the two compounds. TiBeIr2 exhibits superior thermoelectric performance, with a steadily increasing figure of merit (ZT) reaching 0.014 at 1000 K, while HfBeIr2 shows negligible efficiency. The enhanced performance of TiBeIr2 is attributed to its favorable balance between electrical conductivity, Seebeck coefficient, and thermal conductivity. These findings highlight TiBeIr2 as a promising candidate for high-temperature thermoelectric applications.